Greenland, Arch Glacier at Gregory Valley, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
Frankel Land − Gregory Valley, Arch Glacier taken from near campi-lateral moraine on eastern side, Aug 23, 1933